(untitled) (Nepalese Journal of Development and Rural Studies, 2019)
This paper presents effectiveness of service delivery practices of local government in federal context. In doing so, focus was given to analyze opportunities and challenges of administrative service delivery functions of Banganga Municipality of Kapilvastu District located in Province Number 5. This study applied mix method approach in which necessary data are collected from 20 administrative staffs and 100 service receivers selected purposively by applying institutional/exit poll survey, KII, and Observation techniques. The findings reflect the administrative service delivery mechanism becoming more accessible to the citizens. However, physical infrastructure of municipal and ward offices found very poor to offer efficient administrative service delivery to all including people with disabilities. The administrative staffs seem capable for offering efficient administrative service delivery but they are not sufficient. However, the municipality is not institutionally strong in terms of physical facilities. The local representatives also seem more accessible and accountable working with limited physical, economic and human resources. Finally, such challenges must be addressed with proper cooperation and collaboration between and among federation, provincial and local government for making regulatory administrative service delivery functions more effective and efficient.